Magneto-electronic properties of multilayer graphenes. Issue 39 (21st October 2015) - Lin, Chiun-Yan; Wu, Jhao-Ying; Ou, Yih-Jon; Chiu, Yu-Huang; Lin, Ming-Fa
<x xml:space="preserve">Abstract</x> This article reviews the rich magneto-electronic properties of multilayer graphene systems.